2005
DOI: 10.1080/15287390590921793
|View full text |Cite
|
Sign up to set email alerts
|

Review and Analysis of Inhalation Dosimetry Methods for Application to Children’s Risk Assessment

Abstract: Young children have a greater ventilation rate per body weight or pulmonary surface area as compared to adults. The implications of this difference for inhalation dosimetry and children's risk assessment were evaluated in runs of the U.S. Environmental Protection Agency (U.S. EPA) 1994 reference concentration (RfC) methodology and the ICRP 1994 inhalation dosimetry model. Dosimetry estimates were made for 3-mo-old children and adults for particles and Category 1 and 2 reactive gases in the following respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 103 publications
(154 reference statements)
1
61
1
Order By: Relevance
“…It is evident from Figure 3d that infants, for all pathogens studied here, appear to be at a greater risk compared to adults. These findings for infants are consistent with prior studies done with polydisperse radionuclides using the ICRP model (Ginsberg et al 2005) and reactive gases using the NCRP model (Ginsberg et al 2008). Interestingly, our studies are also consistent with Cho et al (2005) who found significantly more deposition of different species of fungi in the lower airways of infants compared to adults.…”
Section: Applicationssupporting
confidence: 83%
See 2 more Smart Citations
“…It is evident from Figure 3d that infants, for all pathogens studied here, appear to be at a greater risk compared to adults. These findings for infants are consistent with prior studies done with polydisperse radionuclides using the ICRP model (Ginsberg et al 2005) and reactive gases using the NCRP model (Ginsberg et al 2008). Interestingly, our studies are also consistent with Cho et al (2005) who found significantly more deposition of different species of fungi in the lower airways of infants compared to adults.…”
Section: Applicationssupporting
confidence: 83%
“…The surface areas of the extrathoracic, tracheobronchial, and alveolar regions for 176 cm adults are 160, 2363, and 777417 cm 2 , respectively, while for 60-cm infants they are 40, 1570, 37704 cm 2 , respectively (Ginsberg et al 2005(Ginsberg et al , 2010. Again, as in Figure 3c, the upper bounds of NRDA i are plotted for three different bioaerosols in Figure 3d.…”
Section: Applicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, infants potentially receive a greater exposure of lung surface to airborne compounds on a body weight basis (Bennett et al, 1996). Ginsberg et al (2005) indicated that the particle dose in the pulmonary region is also likely to be two to four times higher in three-month-old children than in adults, particularly for submicrometre-size particles. The skin surface area relative to body weight is greater in children than in adults, such that the potential dose received following dermal exposure is likely to be about three times greater in infants than in adults (Clewell et al, 2002).…”
Section: Absorption Distribution Metabolism and Eliminationmentioning
confidence: 99%
“…Dosimetric modeling for children inhaling both gases and particles has been recently reviewed (Ginsberg et al, 2005(Ginsberg et al, , 2008Foos & Sonawane, 2008;. Children have age-dependent airway sizes, ventilation patterns, and time-activity behaviors, all of which potentially increase their air-pollutant doses over those of adults.…”
Section: Childrenmentioning
confidence: 99%